2003
DOI: 10.2214/ajr.180.3.1800755
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Malignancy in Complex Cystic Renal Masses (Bosniak Category III): Should Imaging-Guided Biopsy Precede Surgery?

Abstract: Renal biopsy and radiologic follow-up were useful in identifying nonmalignant lesions in complex cystic renal masses and avoided unnecessary surgery in 39% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(80 citation statements)
references
References 9 publications
1
71
0
8
Order By: Relevance
“…2). 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] One evaluated FNA with cytopathology alone 12 and all other studies evaluated core needle biopsy with surgical pathology. There were 15 core biopsy studies that used 18G needles.…”
Section: Resultsmentioning
confidence: 99%
“…2). 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] One evaluated FNA with cytopathology alone 12 and all other studies evaluated core needle biopsy with surgical pathology. There were 15 core biopsy studies that used 18G needles.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is literature supporting the role of RTB for histology identification of Bosniak III and IV cysts. 28,74,75,82 It is generally felt that RTB is not diagnostic for most Bosniak III cysts, as there is minimal targetable solid component. (Level of evidence: 3; Recommendation: D) For Bosniak IV cysts, a biopsy of the solid component may be considered to confirm the presence of a malignant tumour and to help with decisionmaking in select cases (elderly, multiple comorbidities, unfit for treatment, etc).…”
Section: Role Of Renal Tumour Biopsy In the Management Of Cystic Lesionsmentioning
confidence: 99%
“…(Level of evidence: 3; Recommendation: D) For Bosniak IV cysts, a biopsy of the solid component may be considered to confirm the presence of a malignant tumour and to help with decisionmaking in select cases (elderly, multiple comorbidities, unfit for treatment, etc). 5,28,74,75,82,83 (Level of evidence: 3; Recommendation: C) Of interest, some reports have suggested that the combination of fine needle aspiration (FNA) and core biopsy may lead to a slightly higher diagnostic yield than core biopsy alone. 85 Nevertheless, in most centres of experience, RTBs are performed using core biopsy alone, as the combination is thought to add minimal value.…”
Section: Role Of Renal Tumour Biopsy In the Management Of Cystic Lesionsmentioning
confidence: 99%
“…Indications for renal biopsy remains restricted to Bosniak IV cysts with a tissue target clearly visible on imaging. 7 Harisinghani et al 7 report that a combination of biopsy and fine needle aspiration of cyst could prevent 40% of unnecessary surgery for Bosniak III cysts. In a series of 199 biopsies associated with a needle puncture for IIF and III lesions , Lang et al 1 found a positive predictive value of 91% for malignancy and 100% for benign lesions.…”
Section: Contrast Enhanced Ultrasound Of the Kidney (Ceus)mentioning
confidence: 99%